Analisis Kebutuhan Alat Angkut Dump Truck HD 985 Pada Kegiatan Long-Haul Pengangkutan SSP: Analysis of the Need for Dump Truck Conveyance Equipment HD 985 in the Long-Haul Activities of SSP Transportation - Sri Widodo; Kisman Kisman; Arif Nurwaskito (CV Insight Publisher, 2023)
Mining activities must always be supported by mechanical equipment that can work optimally to create satisfactory results with minimal cost and effort. Periodic control must also always be carried out because it relates to the company's production target. This research aims to determine the production of the HD985 dump truck conveyance and obtain the amount of lift needed for screening station product (SSP) transportation activities. This research was conducted using data collection methods in the field, discussions with several employees, and existing literature. Then processing is carried out by calculating data from the area using a specific formula and then analyzing the results of the calculations that have been obtained. Based on estimates, it was found that the production of the HD985 dump truck conveyance reached 69.46 tons/hour. And for the number of rides needed with a target tonnage of 1,000 tons, namely 2 units, for a target of 2,000 tons, 4 units are required; for a target of 3,000 tons, 6 units are needed, for a target of 4,000 tons, 8 units are required, for a target of 5,000 tons, 10 teams are needed.